Peran Kelompok Tani Bajuejayya Terhadap Kesejahteraan Keluarga Moncongkomba Takalar - Muhammad Dinul Islami; Irwanti Said (Jurnal Berita Sosial, 2022)
The role of the Bajuejayya Farmer Group in Improving the Family Economy is carried out together. This type of research is descriptive qualitative. Data was collected by conducting observations, interviews, documentation and reference searches. The data sources used are primary sources and secondary data sources. Data processing and analysis techniques go through three stages, namely: data reduction, data presentation and conclusion drawing. The results of this study indicate the role of the Bajuejayya Farmer's Group, firstly as a facilitator by building joint consensus and organizing the use of resources or in other words making it easier for farmers to get sugarcane seeds. Second, as a community representative, that is related to group interactions including the Bajuejayya Farmer Group with institutions, if there is a dispute, it plays a role in protecting the farmer members who are members of it. The Bajuejayya Farmer's Group is very influential for farmers, because since the Bajuejayya Farmer's Group exists, the farmers can fulfill and even increase their income so that it affects the fulfillment of family welfare.